Hubungan Konsumsi Makanan Fast Food dengan Kejadian Obesitas pada Remaja - Chairil; Isnaniar; Norlita, Wiwik; Oktavia, Nurani (As-Shiha: Jurnal Kesehatan, 2024)
Cases of obesity in adolescents are due to consumption of fast food, foods high in sodium and sugar and a lack of knowledge about choosing healthy foods and supported by a lack of physical activity (Sri and Sari, 2008). Based on the 2013 Riskesdas the prevalence of obesity in Yogyakarta Province in the age group of 13- 15 years is 2.6% and DIY itself is included in 15 provinces with a high prevalence of very overweight or obese (Ministry of Health RI, 2013). Adolescents who are overweight have a 70% risk of experiencing overweight or obesity as adults (Ministry of Health Nutrition & Health, 2016)To determine the relationship between food consumption and the incidence of obesity in adolescents at SMA Muhammadiyah 3 Pekanbaru. This study is a correlation study regarding the habit of consuming fast food (fast food) with the risk of obesity by using a cross sectional. This research was conducted at SMK Muhammadiyah 3 Pekanbaru. with the number of respondents as many as 65 students / i. the instrument or measuring instrument used is research in the form of a Food Frequency Questionnaire (FFQ) questionnaire using an ordinal scale. the sample technique used is simple random sampling. Based on the results of the study, it was found that the consumption habits of adolescents at SMK Muhammadiyah 3 Pekanbaru still sometimes consumed (fast food) as much as 81.5% and not often (fast food) 3.1% often as much as 10.4%) normal body mass index as much as 78.5% and overweight as much as 3.1% and obese 1 18.5%. there is no relationship between consumption of fast food (fast food) and the incidence of obesity in adolescents. It is hoped that adolescents will reduce consumption of fast food and consume healthy foods with balanced nutrition and carry out physical activities such as sports with the aim of increasing weight loss